Reference architecture design for computer-based speech therapy systems. (March 2023) - Attwell, Geertruida Aline; Bennin, Kwabena Ebo; Tekinerdogan, Bedir
Abstract: With the current international shortage of speech-language pathologists (SLPs), there is a demand for online tools to support SLPs with their daily tasks. For this purpose, several online speech therapy systems (OSTSs) have been proposed and discussed in the literature. However, developing these OSTSs is not trivial since it involves the consideration of various functional and quality concerns. Hence, for communicating the design decisions and guiding the development and analysis of these systems, a proper architecture design is important. Unfortunately, the architecture design of OSTSs has not been explicitly addressed in the literature. To this end, we present a reference architecture for OSTSs which has been designed following well-established architecture design methods. The reference architecture captures the reusable design elements of OSTSs and can be used to derive various different application architectures. A case study approach is used to illustrate and validate the use of the presented reference architecture.